Sweet and sour: music and taste associations. Issue 3 (11th May 2015) - Kontukoski, Maija; Luomala, Harri; Mesz, Bruno; Sigman, Mariano; Trevisan, Marcos; Rotola-Pukkila, Minna; Hopia, Anu Inkeri
Abstract : Purpose: – This paper aims to extend current understanding concerning the cross-modal correspondences between sounds and tastes by introducing new research tools and experimental data to study associations and their reflections between music and taste. Design/methodology/approach: – The experiment design addresses the multidisciplinary approach by using cultural, chemical and statistical analysis methods. Findings: – The paper provides further evidence that exposure to the "sweet" or "sour" musical pieces influences people's food-related thinking processes and behaviors. It also demonstrates that sweet or sour elements in the music may reflect to actual sweetness (as measured by sugar content) and sourness (as measured by organic acid content) of foods developed in association with music carrying similar taste characteristics. Research limitations/implications: – The findings should be replicated and expanded using larger consumer samples and wider repertoires of "taste music" and dependent variables. Also, the level of experimental control should be improved; e.g., the "sweet" and "sour" music were produced using different instruments, which may have an influence to the results. Practical implications: – Ambient "taste music" that is congruent with the basic flavors of the dishes can be played in restaurants to highlight guests' sensory experience. Social implications: – By carefully considering the symbolic meanings of the music used in different social situations, it is possible to create multimodal experiences and even subconscious expectations in people' minds. Originality/value: – Cross-modal associations are made between the tastes and music. This can influence on perception of food and provide new ways to build multimodal gastronomic experiences.